2003
DOI: 10.1177/002221940303600205
|View full text |Cite
|
Sign up to set email alerts
|

Instructing Adolescents with Learning Disabilities

Abstract: A previous meta-analysis indicated that eight instructional factors--Questioning, Sequencing and Segmentation, Skill Modeling, Organization and Explicit Practice, Small-Group Setting, Indirect Teacher Activities (e.g., homework), Technology, and Scaffolding-captured the majority of successful intervention programs for adolescents with learning disabilities (LD). Most important was the Organization/Explicit factor, which contributed significant variance (16%) to effect size. This factor included two important i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
104
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(109 citation statements)
references
References 31 publications
1
104
0
4
Order By: Relevance
“…They found that advanced organizers (defined as curriculum adaptations that direct student focus on information that is particularly salient or important in a reading) were successful. Swanson and Deshler (2003) noted that providing educators with specific examples of how to improve upon high quality instructional strategies such as explicit practice by combining them with content enhancement routines or learning-strategy instruction is also critical to improving outcomes for students with disabilities. Pugach and Warger (2001) observed that the access mandates shift the focus of the "problem" to be solved when teaching students with disabilities from fixing or changing the student to examining the relationship between the student and the curriculum and, when necessary, modifying the curriculum to enable student learning.…”
Section: Practitioners Often Interpret Promoting "Access To Thementioning
confidence: 99%
“…They found that advanced organizers (defined as curriculum adaptations that direct student focus on information that is particularly salient or important in a reading) were successful. Swanson and Deshler (2003) noted that providing educators with specific examples of how to improve upon high quality instructional strategies such as explicit practice by combining them with content enhancement routines or learning-strategy instruction is also critical to improving outcomes for students with disabilities. Pugach and Warger (2001) observed that the access mandates shift the focus of the "problem" to be solved when teaching students with disabilities from fixing or changing the student to examining the relationship between the student and the curriculum and, when necessary, modifying the curriculum to enable student learning.…”
Section: Practitioners Often Interpret Promoting "Access To Thementioning
confidence: 99%
“…Diğer öğrencilerle karşılaştırıldığında, okumada güçlük yaşayan öğrenciler okuma etkinliklerine çok daha az zaman ayırmaktadırlar (Swanson ve Deshler, 2003). Bu durum öğrencilerde olumsuz benlik algısına, okuma etkinliklerine karşı ilgi duymama, kendine güvensizlik gibi olumsuz sonuçlar doğurmaktadır.…”
Section: öğRenme Güçlüğü Terimi Milli Eğitim Bakanlığı'nın (Meb) 2006unclassified
“…However, there are relatively few resources for helping teachers and administrators understand meta-analysis and the use of ES as they seek to implement educational reform on the basis of research-based evidence (Banda & Therrien, 2008;Swanson & Deshler, 2003).…”
Section: Associate Editor's Columnmentioning
confidence: 99%